Barilius signicaudus, a new species of cyprinid fish from Maeklong Basin, western Thailand (Cypriniformes: Cyprinidae) - Tejavej, Anuratana (Zootaxa, 2012)
Barilius signicaudus, a new species of cyprinid fish from the Khwae Noi and Khwae Yai branches of the Maeklong River,western Thailand, is described. It is characterized by the combination of a large, elongated blotch at the caudal-fin base(blotch is formed by the fusion of the large caudal spot at the fleshy end of the caudal base and the last vertical bar on theflank) that extends about 1/3 of the distance from the caudal-fin origin beyond the last scale on the caudal base to the mar-gin of the caudal fork; an anal-fin origin opposing the 2nd–4th branched dorsal-fin rays; eight scale rows above the lateralline; dark pigment on the dorsal fin concentrated mainly along the margins of the rays; 36 or more precaudal lateral-linescales; and small dentary tubercles. This species has previously been identified as Barilius pulchellus and Barilius orna-tus. Barilius pulchellus has no, or a small caudal spot, a dorsal fin with dark pigments concentrated in the middle of theinterradial regions, and much larger dentary tubercles. Barilius ornatus and similar species have an anal-fin position thatopposes the 5th–7th branched dorsal-fin rays (rarely the 4th), or does not overlap with them at all, and have no, or small caudal spots.